Work readiness in final-year students: The predictive value of work motivation and social support - Rizqianto, Indra Dwi; Hidayat, Muhammad (Universitas Ahmad Dahlan, 2025)
In 2023, Indonesia reported approximately 7.86 million unemployed individuals, with a notably low employment absorption rate among university graduates. One contributing factor to this issue is the insufficient level of job readiness among graduates, which hinders their ability to secure employment. This study aims to examine the extent to which work motivation and social support predict job readiness among final-year students at Ahmad Dahlan University. The research involved 100 participants selected through purposive sampling, a form of non-probability sampling. A quantitative research approach was employed, utilizing validated scales to measure job readiness, work motivation, and social support. Content validity was established through expert judgment. Data were analyzed using multiple linear regression via SPSS version 16.0. The findings indicate that work motivation and social support collectively predict job readiness. However, while work motivation significantly contributes to job readiness, social support does not show a statistically significant effect. These results underscore the crucial role of internal factors particularly individual motivation in enhancing the job readiness of final-year students as they transition into the workforce, particularly within the context of the Indonesian labor market.